Challenges in Patient Enrollment and Retention in Clinical Studies for Alcoholic Hepatitis: Experience of the TREAT Consortium. (27th October 2017) - Comerford, Megan; Lourens, Spencer; Liangpunsakul, Suthat; Chalasani, Naga P.; Sanyal, Arun J.; Shah, Vijay H.; Kamath, Patrick S.; Puri, Puneet; Katz, Barry P.; Radaeva, Svetlana; Crabb, David W.
Abstract : The TREAT Consortium has carried out clinical studies on alcoholic hepatitis (AH) for over 4 years. We encountered problems with participant recruitment, retention, and eligibility for specific protocols. To improve our ability to carry out such trials, we reviewed recruitment screening logs, end of study logs, and surveyed study coordinators to learn the reasons for missing patients, why patients declined enrollment, and the number of patients eligible for treatment trials. Associations of the recruited subjects' demographics with their adherence to follow‐up appointments were examined. Three hundred eight‐seven patients (AH and heavy drinking controls) were enrolled in the observational study, and 55 AH patients were recruited into treatment trials. About half of patients identified with AH could not be recruited; no specific reason could be determined for about two‐thirds of these. Among the patients who gave a reason for not participating, the most common reasons were feeling too sick to participate, desire to concentrate on abstinence, and lack of interest in research. Approximately a quarter of the AH patients met eligibility criteria for treatment trials for moderate or severe AH and we were able to recruit half to two‐thirds of those eligible. Approximately 35% of participants in the observational study returned for both 6‐ and 12‐month follow‐up visits. We did not identify biopsychosocial or demographic correlates of retention in the study. This analysis revealed that attempts at recruitment into trials for AH miss some subjects because of structural issues surrounding their hospital admission, and encounter a high rate of patient refusal to participate. Nonetheless, more than half of the patients who met the eligibility criteria for moderate or severe AH were entered into clinical trials. Retention rates for the observational study are relatively low. These findings need to be accounted for in clinical trial design and power analysis. Abstract : Recruitment and retention of patients with alcohol use disorders in clinical trials is difficult; we report factors related to recruitment of patients with alcoholic hepatitis into observational and treatment trials. Approximately 35% of patients in the observational study returned for 6 and 12 months followup visits. We did not identify any biopsychosocial correlates of retention. Half of the patients eligible for the treatment trials could be recruited. These data may guide design, power analyses, and execution of future studies.